Effects of Cyhalothrin-Based Pesticide on Early Life Stages of Common Carp (Cyprinus carpio L.) - Richterová, Zuzana (Hindawi Publishing Corporation, 2014)
The effects of Nexide (a.i. gamma-cyhalothrin 60 g L(−1)) on cumulative mortality, growth indices, and ontogenetic development of embryos and larvae of common carp (Cyprinus carpio L.) were studied. Levels of oxidative stress parameters glutathione reductase (GR), glutathione peroxidase (GPx), catalase (CAT), glutathione-S-transferase (GST), and lipid peroxidation were determined. Eggs of newly fertilised common carp were exposed to Nexide at concentrations 5, 25, 50, 100, and 250 μg L(−1) (0.3, 1.5, 3, 6, and 15 μg L(−1) gamma-cyhalothrin). All organisms exposed to concentrations higher than 50 μg L(−1) died soon after hatching; at 25 μg L(−1), 95% mortality was recorded. Larvae exposed to 5 μg L(−1) showed significantly lower growth and retarded ontogenetic development compared to control. Histological examination of the livers of larvae from the exposed group revealed dystrophic changes. The value of detoxification enzyme GST of organisms from the exposed group was significantly higher compared to the control and the value of defensive enzyme GPx was significantly lower compared to the control. The results of our investigation confirmed that contamination of aquatic environment by pesticides containing cyhalothrin may impair growth and development of early life stages of carp and cause disbalance of defensive enzymes.